2012
DOI: 10.1364/oe.20.011351
|View full text |Cite
|
Sign up to set email alerts
|

Circular motion of particles suspended in a Gaussian beam with circular polarization validates the spin part of the internal energy flow

Abstract: Non-spherical dielectric microparticles were suspended in a water-filled cell and exposed to a coherent Gaussian light beam with controlled state of polarization. When the beam polarization is linear, the particles were trapped at certain off-axial position within the beam cross section. After switching to the right (left) circular polarization, the particles performed spinning motion in agreement with the angular momentum imparted by the field, but they were involved in an orbital rotation around the beam axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 29 publications
1
65
0
Order By: Relevance
“…It is a part of a general class of studies in which particles are observed to undergo circulation while immersed in a static force field with nonzero curl (25,49). In addition, Angelsky et al observed orbital angular momentum transfer in circularly polarized Gaussian beams as a manifestation of the macroscopic "spin energy flow," thus confirming the theory of inhomogeneously polarized paraxial beams (34,50).…”
Section: The Evanescent Wave Technique As a Methods Of Angular Momentumentioning
confidence: 91%
See 1 more Smart Citation
“…It is a part of a general class of studies in which particles are observed to undergo circulation while immersed in a static force field with nonzero curl (25,49). In addition, Angelsky et al observed orbital angular momentum transfer in circularly polarized Gaussian beams as a manifestation of the macroscopic "spin energy flow," thus confirming the theory of inhomogeneously polarized paraxial beams (34,50).…”
Section: The Evanescent Wave Technique As a Methods Of Angular Momentumentioning
confidence: 91%
“…This motion is of theoretical and practical interest as it arises due to the particle's interaction with the inherently anisotropic mechanical environment nearby a solid interface as it moves in response to a periodic driving force. It has several distinguishing features that may make it an applicable technique for generating orbital angular momentum, alongside existing methods predominantly using structured beams carrying orbital or spin angular momentum (30)(31)(32)(33)(34)(35)(36) Forces on an Optically Driven and Trapped Microsphere An optically trapped microsphere in fluid is well-modeled as a stochastically driven, damped harmonic oscillator in three dimensions (37, 38):[1]The terms on the right of Eq. 1 correspond, in order, to the restoring force of the optical trap, the dissipative drag in fluid, the stochastic force due to thermal fluctuations, and an externally applied force.…”
mentioning
confidence: 99%
“…According to the experiment suggested in the study [25], these are the particles peculiar for the golden hydrosol (of about 1 nm and 100 nm in size; considered at the room temperature). The mechanical influence of spin flows [26,27] on the motion of these particles is not dealt with hereafter. Let us analyse formation of the optical force opt ε being the dielectric permittivities of the gold particle and the surrounding medium, respectively).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Zhang et al [18] generated the OAM ±2 modes composed of HE 31 even ± iHE 31 odd in a four-mode fiber (4MF) by using an acoustically induced fiber grating. However, these published works lack analysis in the photonics spin of the generated OAM beams, which is not only a fundamental physical question but also a crucial factor in multiplexing [7] and micro-particles manipulation system [21][22][23].…”
Section: Introductionmentioning
confidence: 99%